Ocular Diseases at the Medical-Surgical Clinic Ophthalmology of Brazzaville - Fredy, Nganga Ngabou Charles Géraud; Chantal, Makita; Vissimy, Onka; Reinette, Messe Ambia Koulimaya; Benedicte, Diatewa; Eyissa, Gombe; Francine, Alandzobo (Journal of Ophthalmology and Research, 2019)
The causes of blindness are diverse, including infectious (dominated by trachoma and onchocerciasis) and non infectious. The objective of this study was to identify the most common ocular diseases in ophthalmology consultation. Patients and methods: This was a retrospective descriptive study, based on information collected from medical records at the medical-surgical clinic Ophthalmology of Brazzaville. The study period was from January 1 to December 31, 2018, a period of 1 year. All patients who consulted during the study period were included. The variables studied were age, sex, motive for consultation and diagnosis. Results: Our sample consisted of 908 females versus 528 males, or a sex ration of 0.58. It was represented by 10.72% of patients under 15 years against 21.58% of patients over 60 years. Overall, the most common ocular disease were refractive errors followed by conjunctivitis. Cataracts were the third leading cause of consultation with 12.39% of cases followed by glaucoma with 6% of cases. Conclusion: Ocular diseases in private ophthalmology practice in Brazzaville remain dominated by conjunctivitis and refractive errors, followed by cataract and glaucoma. We found no cases of trachoma or onchocerciasis.